Narasi Green Development dalam Kebijakan Hilirisasi Nikel Indonesia: Analisis Wacana Kritis atas Kebijakan dan Kontestasi Makna - Mangihut Siregar; Achmat Shu'Udin (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study analyzes the construction and contestation of the “green development” narrative within Indonesia’s nickel downstreaming policy, particularly in the Sulawesi region. Using a Critical Discourse Analysis (CDA) approach, the study examines how the state and corporations form a discursive coalition that dominates the policy space, as well as how counter-narratives from civil society critique the social and ecological impacts of mining expansion. The findings show that the dominant narrative emphasizes energy transition and economic growth, while overlooking agrarian conflicts, pollution, and the marginalization of local communities. A crosstab analysis of five types of policy documents indicates that public involvement remains very limited, with the majority of policy formulation processes taking place without substantive participation. This condition reveals an imbalance in the deliberative structure and the exclusion of meaning within the policy process. The study concludes that the green development narrative in nickel policy has functioned as a political-economic instrument of legitimation that sacrifices ecological justice. Institutional reform is therefore required to ensure spaces for public participation and recognition of local community narratives as part of a just and sustainable energy transition.